CPEC's utility and concerns under OBOR initiative: A Pakistani industrial perspective - Ghulam Abbas; Zhiming Liu; Shahbaz Hassan Wasti; Uzma Munir; Muhammad Abbas (Economies, 2019)
This study emphasizes the utility and concerns of China Pakistan Economic Corridor (CPEC) on various sectors of Pakistan's economy through the lens of real stakeholders. Specifically, this study focuses on three aspects: the beneficiary of CPEC; CPEC's effects on employment, GDP, foreign direct investment and personal income in Pakistan; and the concerns regarding Pakistan's sovereignty. A qualitative research approach was adopted to explore the objectives of the study. To analyze these aspect, in-depth interviews from different Pakistan's business community are conducted. Our study finds that CPEC will not only beneficial for both Pakistan and China, but also for other neighbouring countries in the region. To validate these findings, interviewee's data is analyzed in the light of semantic analysis approach. Our study illustrates that, the development along the corridor will produce employment opportunities that will raise the income level of a common person of Pakistan, and the industrial growth in Pakistan through CPEC will have a positive effect on the country's GDP. Our study also concludes that CPEC doesn't pose any threat to Pakistan's sovereignty. The stakeholders of CPEC are concerned over the intentions of Pakistan government; that need to be clarified. This research study also suggests the maximum benefits out of this mega venture.
Keywords: 330; CPEC; game-changer; OBOR; Pakistan economy